2003
DOI: 10.1073/pnas.1132018100
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose 6-phosphate is indispensable for carbohydrate utilization and growth in Arabidopsis thaliana

Abstract: Genes for trehalose metabolism are widespread in higher plants. Insight into the physiological role of the trehalose pathway outside of resurrection plant species is lacking. To address this lack of insight, we express Escherichia coli genes for trehalose metabolism in Arabidopsis thaliana, which manipulates trehalose 6-phosphate (T6P) contents in the transgenic plants. Plants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

40
497
3
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(553 citation statements)
references
References 52 publications
40
497
3
7
Order By: Relevance
“…Although hypocotyl elongation arises from cell expansion rather than growth through increases in cell number (Gendreau et al, 1997), our data are consistent with studies demonstrating that Tre6P metabolism is a crucial regulator of growth responses to Suc. For example, Arabidopsis seedlings overexpressing the bacterial Tre6P phosphatase otsB, which reduces [Tre6P], accumulate less biomass compared with the wild type when supplemented with Suc (Schluepmann et al, 2003). The converse is also true; otsA (TPS) overexpressors, in which [Tre6P] is increased, accumulate more biomass than the wild type when supplemented with Suc (Schluepmann et al, 2003).…”
Section: Phytohormone Signaling and Suc-induced Hypocotyl Elongationmentioning
confidence: 71%
See 2 more Smart Citations
“…Although hypocotyl elongation arises from cell expansion rather than growth through increases in cell number (Gendreau et al, 1997), our data are consistent with studies demonstrating that Tre6P metabolism is a crucial regulator of growth responses to Suc. For example, Arabidopsis seedlings overexpressing the bacterial Tre6P phosphatase otsB, which reduces [Tre6P], accumulate less biomass compared with the wild type when supplemented with Suc (Schluepmann et al, 2003). The converse is also true; otsA (TPS) overexpressors, in which [Tre6P] is increased, accumulate more biomass than the wild type when supplemented with Suc (Schluepmann et al, 2003).…”
Section: Phytohormone Signaling and Suc-induced Hypocotyl Elongationmentioning
confidence: 71%
“…For example, Arabidopsis seedlings overexpressing the bacterial Tre6P phosphatase otsB, which reduces [Tre6P], accumulate less biomass compared with the wild type when supplemented with Suc (Schluepmann et al, 2003). The converse is also true; otsA (TPS) overexpressors, in which [Tre6P] is increased, accumulate more biomass than the wild type when supplemented with Suc (Schluepmann et al, 2003). Therefore, our data using tps1 mutants as a proxy for altered Tre6P metabolism provide new evidence to support the notion that Tre6P promotes growth under conditions of increased Suc availability (Schluepmann et al, 2003;Zhang et al, 2009).…”
Section: Phytohormone Signaling and Suc-induced Hypocotyl Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that T6P has a regulatory role in carbohydrate utilization during plant growth and development (Eastmond et al 2002;Schluepmann et al 2003Schluepmann et al , 2004van Dijken et al 2004). We have reported before that overexpression in Arabidopsis of its AtTPS1 homolog leads to a glucose and abscisic-acid insensitive phenotype and to stress tolerance, suggesting that trehalose metabolism plays an important role in signaling gene regulation to integrate environmental and metabolic cues during vegetative development (Avonce et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of the Arabidopsis AtTPS1 gene in its homologous background does not produce such drastic eVects but still there is a delay in Xowering (Avonce et al 2004). The accumulation of higher levels of T6P are probably causing these defects since T6P has turned out to be a Wne-tuned signaling molecule that has a regulatory role in carbohydrate utilization during plant growth, embryo development and Xowering (Eastmond et al 2002;Schluepmann et al 2003Schluepmann et al , 2004van Dijken et al 2004). Therefore, it was decided to construct a bifunctional TPS-TPP enzyme, which while maintaining trehalose biosynthesis capacity would not lead to excess accumulation of free T6P in the cytosol avoiding undesired secondary eVects in the transgenic plants.…”
Section: Discussionmentioning
confidence: 99%